Urban Image in Iranian Fiction Films - Azam Ravadrad; Baharak mahmoodi (Taḥqīqāt-i Farhangī-i Īrān)
Tehran as a symbol of Iranian modernity has been considered in many Iranian fiction films. Representation of Tehran in cinema can be the representation of Iranian modernity revolution. This study focuses on the representation of urban image in Iranian fiction films through critical theories such as Simmel or Benjamin opinions. In this article we discus about the mediator role of cinema for representing the Urban life Image and confliction of modernity in Iran.Meanwhile some megalopolis such as Paris, Berlin, Moscow, New York and sanpitersboorg est.…have had great opportunity for understanding confliction of modernity in their situation, Tehran has never have that chance. Regarding to this vacuum we want to explain the role of Iranian fiction films for understanding the entrance of modernity consequences in different eras. We believed that fiction films can represent confliction of city and village, represent of modern dualities, non cohesive rationality and many other gaps in Iranian modernity that we have to know.